DAMPAK PENILAIAN PRESTASI KERJA TERHADAP PROMOSI JABATAN PADA SEKOLAH PERMATA HARAPAN II BATAM - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
Human Resources has an important role in a company. Company is a tool to achieve goals that must be able to provide clarity of status to someone in the working environment, both in terms of ties, position and role. One of the efforts to improve the effectiveness of work is the assessment of employee performance against promotion of office. Performance appraisal is the employee's psychological bond to the company, the willingness to work hard and the desire to further increase in the career. Improving the company's capabilities requires performance changes with changes in system variables, strategic objectives and control systems, interpersonal relationships. In the corporate environment there is a culture of work that is a culture, norms and habits that apply everyday. This study examines the relevance of employee performance appraisal to promotion of positions at Permata Harapan II Batam School. By using linear regression analysis of one independent variable, the result shows that there is influence between employee performance appraisal to promotion of position. Implementation of employee performance appraisal gives the most dominant influence. Employee performance appraisal on promotion positively affects the effectiveness of work at Permata Harapan II Batam School.